Numerical modeling of the process of pressing steel billet - Rogovoy Аnatoliy Аlekseevich; Salikhova Nelly Кamilevna (Computational Continuum Mechanics, 2014)
The study is concerned with numerical modeling of the process of pressing of a steel billet (steel 30HGSA). The initial billet had a form of octahedral truncated pyramid. The modeling process was carried out in accordance with a manufacturing scheme that involves the upset forging of a billet (pyramid) uniformly heated to a predetermined temperature, its unloading, pressing using special tools (stand and punching die) in a direction perpendicular to the previous one, and subsequent unloading upon completion of the process. Using the Ramberg-Osgood equation and the reference data on the mechanical properties of steel 30HGSA at temperature 500ºС, the deformation curve was plotted. The stress-strain state of the billet and its forming were determined at each stage of the forming operation with account for large plastic deformations and material’s nonlinear properties. In compliance with the manufacturing scheme, a solution to the nonlinear elastic-plastic problem dealing with the study of the upset forging of a steel billet and its subsequent unloading was found. It was established that after unloading of the billet the plastic strain rate remains practically unchanged (because of small elastic deformations), while the resultant stress varies considerably. The lateral surface of the body at the end of the upset forging (by 29.3%) had the form of a convex full roll. A series of computational experiments was performed to study the accuracy of the finite element solutions for the process of upset forging of the billet at different degrees of discretization of the computational domain. The results obtained were used for numerical modeling of the following operating steps: pressing of the billet with the aid of deformation tools and its unloading. As in the case of upset forging, in the billet there remain significant residual stresses related to the inhomogeneity of plastic deformations occurred during the pressing of the body under study. All simulations were performed in the framework of increments plastic flow theory, using the finite element software SIMULIA/Abaqus with a step-by-step procedure and the Newton-Raphson method for solving the elastic-plastic problem at each step.